Tax measures promoting cooperatives: A fiscal driver in the context of the sustainable development agenda - Alberto Vaquero García; Maria Bastida; Miguel Ángel Vázquez Taín (European Research on Management and Business Economics (ERMBE), 2020)
The social economy (SE) is becoming increasingly present in the Spanish business network. Its special characteristics make it attractive for the development of economic activities, since they are respectful of the environment and they promote the creation of stable and quality employment, even in economically degraded areas or for groups with labour market integration problems. These characteristics, moreover, are particularly important for the consolidation of a new business network that combines economic growth and sustainability, in the context of the commitments undertaken in the 2030 Agenda for the Sustainable Development Goals (SDGs). Cooperatives are the most common SE business model, to the extent that their study comprises an important part of the Spanish economy. The peculiarities of this legal formula, the aids for its constitution and their tax benefits provide important incentives for the constitution of such entities. The aim of this paper is to study the fiscal framework of cooperatives in Spain within the European framework, to determine the extent to which it favours the development of this business model and to identify the bases for improvement that can foster this entrepreneurial model. The analysis of the fiscal data available confirms that the tax advantages for cooperatives, as well as the need to update fiscal policies to the current economic context, have diluted over time. Finally, the need to extend to cooperatives some of the tax benefits designed for other business models is pointed out.
Keywords: J16; L31; R11; 650; Cooperative enterprises; Entrepreneurship; Fiscal benefits; Sustainability; Taxes